2007
DOI: 10.1111/j.1600-6143.2007.01997.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion Suppresses Cardiac Allograft Vasculopathy in Mice

Abstract: Cardiac allograft vasculopathy (CAV) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 48 publications
6
80
0
1
Order By: Relevance
“…Experimental strategies of monocyte/M depletion are limited and strategies involving the administration of antibodies, carrageenan, or liposomal clodronate have previously been used (7,28,29). In this study, we used CD11b-DTR mice that have previously been used to demonstrate a key role for resident and infiltrating M in peritonitis (15), pleurisy (14), nephrotoxic glomerulonephritis (9), and hepatic injury/ fibrosis (24).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Experimental strategies of monocyte/M depletion are limited and strategies involving the administration of antibodies, carrageenan, or liposomal clodronate have previously been used (7,28,29). In this study, we used CD11b-DTR mice that have previously been used to demonstrate a key role for resident and infiltrating M in peritonitis (15), pleurisy (14), nephrotoxic glomerulonephritis (9), and hepatic injury/ fibrosis (24).…”
Section: Discussionmentioning
confidence: 97%
“…Macrophages (M) are central to many innate immune responses to injury and some evidence suggests that M can promote acute allograft rejection (6) and the chronic vasculopathy of murine cardiac allografts (7). Furthermore, the presence of M infiltration is of prognostic importance in human renal transplantation (8).…”
mentioning
confidence: 99%
“…Although allograft vessels are likely to be sterile and devoid of PAMPs (unless infected by CMV, see above), they may be injured and release PAMPs that can activate macrophages to produce mitogens for SMCs. Depletion of macrophages can reduce CAV in mouse models, but the adaptive immune system is intact in these models and activated T cells can serve to direct the macrophage response 38 . It seems likely that NK cells and macrophages also play a role in human CAV as such cells are present in the lesions in patterns similar to what has been seen in mouse models 39 , but there are no data in humans to support a role for these cells independent of adaptive immunity.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Also, minor antigenmismatched heart transplants in mice do not elicit donor-reactive antibodies, yet the mice develop significant CAV, suggesting that other mediators of chronic rejection exist (7). Although some studies have shown that NK cells, T cells, macrophages, IFN-γ, and TNFR contribute to CAV (9)(10)(11)(12)(13), the concomitant potential effects of antibodies and/or B cells were not excluded in these studies. In addition to producing antibodies, B cells influence T cell responses by mechanisms such as antigen presentation, cytokine production, costimulation, and organization of splenic lymphoid architecture required for productive immunity (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%